Relationship between of short-course preoperative radiotherapy and serum albumin level and postoperative complications in rectal cancer surgery - Trifunović, Bratislav; Kršić, Jovan; Bezmarević, Mihailo; Grbović, Dragan; Zeljković, Dejan; Nešković, Branimir; Soldatović, Ivan; Prelević, Rade; Mirković, Darko (Vojnosanitetski pregled, 2015)
Background/Aim. The identification of risk factors could play a role in improving early postoperative outcome for rectal cancer surgery patients. The aim of this study was to determine the relationship between short-course preoperative radiotherapy (RT), serum albumin level and the development of postoperative complications in patients after anterior rectal resection due to rectal cancer without creation of diverting stoma. Methods. This retrospective study included patients with histopathologically confirmed adenocarcinoma of the rectum with the clinical stage of T2-T4 operated on between 2007 and 2012. All the patients underwent open anterior rectal resection without diverting stoma creation. Preoperative serum albumin was measured in each patient. Tumor location was noted intraoperatively as the distance between the inferior tumor margin and anal verge. Tumor size was measured and noted by the pathologist who assessed specimens. Some of the patients received short-course preoperative RT, and some did not. The patients were divided into two groups (group 1 with short-course preoperative RT, group 2 without short-course preoperative RT). Postoperative complications included clinically apparent anastomotic leakage, wound infection, diffuse peritonitis and pneumonia. They were compared between the groups, in relation to preoperative serum albumin level, patient age, tumor size and location. Results. The study included 107 patients (51 in the group 1 and 56 in the group 2). There were no significant difference in age (p = 0.95), gender (p = 0.12) and tumor distance from anal verge (p = 0.53). The size of rectal carcinoma was significantly higher in the group 1 than in the group 2 (51.37 ± 12.04 mm vs 45.57 ± 9.81 mm, respectively; p = 0.007). The preoperative serum albumin level was significantly lower in the group 1 than in the group 2 (34.80 ± 2.85 g/L vs 37.55 ± 2.74 g/L, respectively; p < 0.001). A significant correlation between the tumor size and the serum albumin level was found (p = 0.042). Overall, postoperative complications were observed in 13 (25.5%) patients in the group 1 and in 10 (17.8%) patients in the group 2 without significant difference between the groups (p = 0.18). A significantly lower level of serum albumin was found in patients with postoperative complications and in those who died. A significant difference in anastomotic leakage occurrence between groups was found (p = 0.039). Male gender and the lower level of serum albumin were significant predictors for anastomotic leakage occurrence (p = 0.05 and p = 0.002, respectively), but preoperative RT had no significant impact on it. Conclusions. A lower serum albumin level, but not short-course of preoperative RT, was significantly associated with postoperative complications development after rectal resection without diverting stoma.
Keywords: rectal neoplasms; radiotherapy; adjuvant; surgical procedures; operative; treatment outcome; postoperative period; risk factors; serum albumin